Dietary-related characteristics and cataract risk: evidence from a mendelian randomization study - Chen Li; Yicheng Lu; Mingxuan Chen; Qing Zhang; Zhe Zhang; Wenqun Xi; Weihua Yang (Experimental Biology and Medicine, 2025)
Cataract is the leading cause of blindness globally, imposing a significant socioeconomic burden. While diet is associated with various eye diseases, the causal relationship between dietary-related characteristics (DRCs) and cataract remains unclear. This study investigates the causal associations between DRCs and cataract using Mendelian randomization (MR) to provide insights into potential dietary interventions for cataract prevention. We conducted a two-sample MR analysis using data from the open GWAS database, focusing on individuals of European descent. Instrumental variables were selected based on stringent criteria, and multiple MR methods were applied to estimate causal effects. Sensitivity analyses assessed the robustness of the findings. Significant causal associations were found between oily fish intake (OR = 0.86) and variation in diet (OR = 1.26) with cataract. Sensitivity analyses supported the robustness of these findings. Mediation effect analysis suggested that the intake of oily fish might indirectly influence cataract risk through metabolites. This study provides evidence for causal relationships between specific DRCs and cataract, highlighting the potential role of dietary interventions in cataract prevention.